Using the analytic hierarchy process when choosing an online course in media literacy - Rudenko, Yuliia (Educological discourse, 2023)
The article examines the use of Thomas Saati’s Analytic Hierarchy Process for decision-making regarding the choice of an online non-formal education course. The significance of the problem of choosing among alternatives and making a final decision in the pedagogical field is shown. Reasoned simplicity, convenience, and universality of the method. The application of the method in the given task is considered: the selection of an online course on information hygiene (info media literacy) for students of higher education among three offered online platforms of non-formal education. The method’s stages and implementation in the spreadsheet processor Електронній таблиці are described in detail. The first stage is modeling the problem of choosing an online course as a hierarchy containing the goal of decision-making, alternatives for achieving it, and criteria for evaluating alternatives. At this stage, the goal "Formation of information hygiene (info media literacy) of students of higher education" was formed, five criteria for making a decision about the course were defined and described, and 3 alternative online courses were selected. Among the criteria: understanding how the media work (K1); critical thinking (K2); fact-checking (K3); social behavior (K4); emotional and psychological stability (K5). The second stage is prioritization through a series of pairwise comparisons. A table of pairwise comparisons was created, local priorities for the criteria of five criteria were determined, and their consistency indices were estimated. The third stage is the analysis of the priorities of alternative courses. Determining the priority of alternative courses took place according to a similar methodology. The maximum values of the priority vectors for the criteria were calculated, and the consistency ratio was estimated. As a result of the calculations, the course with the highest priority was chosen - alternative A1 (the course "Media literacy: practical skills", published on the online platform of the public project of mass open online courses "Prometheus"). The importance of the method for teachers who have difficulties with choosing a course is proven, and the prospects for further research are outlined, such as the popularization of the method and the development of a software application for automating calculations when making decisions.